2012
DOI: 10.1007/s00277-012-1633-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin D deficiency and anemia in a hospitalized geriatric population: denutrition as a confounding factor

Abstract: This study aimed to investigate the association between vitamin D deficiency and anemia in a hospitalized geriatric population. An observational study, at the acute care geriatric unit of Brest Hospital, France, was conducted among 226 patients aged ≥70 years consecutively hospitalized between January 22, 2010 and August 9, 2010. Vitamin D and hemoglobin levels were measured. Vitamin D deficiency was defined as a 25(OH)D level <50 nmol/L and anemia as defined by the World Health Organization. After adjustment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…Our metaanalysis showed significant between-study heterogeneity, and then we carried out sensitive analysis using I 2 450% as the criterion. After exclusion of two article 16,20 that was key contributors to the between-study heterogeneity, we found no significantly different OR.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Our metaanalysis showed significant between-study heterogeneity, and then we carried out sensitive analysis using I 2 450% as the criterion. After exclusion of two article 16,20 that was key contributors to the between-study heterogeneity, we found no significantly different OR.…”
Section: Discussionmentioning
confidence: 59%
“…Another 20 papers were excluded because association of interest was not evaluated, requested data were not reported, of duplicate papers of the same studies, Finally, seven studies matched the selection criteria and were suitable for our metaanalysis. [16][17][18][19][20][21][22] Three of these studies were cross-sectional, one study was a historical cohort study and three studies were case-control studies. A flow-diagram for the selection of studies to include in our meta-analysis is shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that vitamin D deficiency was independently associated with lower hemoglobin levels and anemia in this specific situation. On the other hand, Coutard et al 24 investigated whether vitamin D deficiency was associated with anemia in 226 hospitalized older French aged ≥70 years and found that although 67.7% and 53.5% of the anemic and non-anemic groups had vitamin D deficiency (p<0.04), this association disappeared after adjusting for albuminemia. The authors emphasized that their finding contradicts earlier studies that had not adjusted for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although some pieces of evidence suggest an association between levels of 25(OH)D and hemoglobin, the literature is still divergent on the topic, so further studies are needed. Moreover, most studies that reported the association were conducted on population subgroups with specific clinical conditions that make them much more vulnerable to the development of anemia, such as chronic renal failure or terminal diabetics 15, hospitalization 24 , disease 26,27 , HIV infection 28 , and congestive heart failure 29 .…”
Section: Discussionmentioning
confidence: 99%